RESPONSE OF GROWING YANKASA RAMS TO GROUNDNUT HAULMS BASED TOTAL MIXED RATIONS WITH DIFFERENT PROTEIN AND ENERGY SOURCES - Bashir, Z.M.; Abubakar, M.; Sani, I.; Matinja, U.I. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study was conducted to evaluate the feed intake, growth performance, rumen metabolites, as well as blood profile of growing Yankasa rams fed groundnut haulms based total mixed rations with different protein and energy sources. A total of 16 Yankasa rams weighing averagely 16.50 kg were assigned to four dietary treatments (16% crude protein) formulated to include: 1 (Cotton seed cake/Wheat offal), 2 (Cotton seed cake//Maize offal), 3 (Groundnut cake/Wheat offal) and 4 (Groundnut cake/Maize offal) such that the two ingredients collectively contributed 67.50% of the diets. The experiment, which lasted for 70 days, was conducted in a Completely Randomized Design, with four (4) treatments of four (4) animals each. The results of daily weight gain (DWG g/day) indicated a significant (P<0.05) difference across the treatments. DWG for animals on diet 4 (104.50 g/day) was significantly higher than those on the other diets. Animals on diet 1 recorded the lowest DWG of 60.00 g/day. However, all animals gained weight, which indicated that, the intake of energy and proteins were well above maintenance requirements. The result of the daily feed intake (DFI) of the animals revealed a significant (P<0.05) difference across the diets. The mean value of the DFI for animals on diets 4(772.36g/day) and 2(772.36g/day) were significantly higher than those for the other diets. Animals on diet 3 recorded the least value (576.59g/day). Feed conversion ratio (FCR) values of animals fed the test diets indicated a significant (P<0.05) difference across the treatments. Animals on diet 1 gave the best FCR value (7.28) compared to those on the other diets with animals on diet 2 having the least efficiently utilised diet (10.04). The results of haematological and serum biochemical parameters indicated that most of the parameters were within the normal values recommended for sheep indicating that the animals were healthy. The pH (Before and After) feeding (6.38 – 6.88 and 6.78 – 7.18) and Rumen ammonia nitrogen (RAN) before (10.78-20.18mg/100ml) and after (20.18 - 25.15mg/100ml) feeding were within recommended values for proper function of rumen. The RAN levels observed in the study suggest enhanced protein degradation and ammonia production, potentially due to the high proportion of groundnut haulms, which is known for its higher protein content. Total VFA concentrations increased after feeding (10.23 - 11.53mmol/100ml) across the diets, suggesting different levels of carbohydrate fermentation across the diets. From the results of the current study, based on the higher weight gains of 104.50g/day and normal levels of haematological and serum biochemical parameters and optimum RAN and total VFA production, diet 4 (Groundnut cake/Maize offal) is recommended for growing Yankasa rams.